Earnings response coefficients in the Greek market - Maditinos, Dimitrios I.; Šević, Željko; Stankevičienė, Jelena; Karakoltsidis, Nikolaos (Journal of Business Economics and Management, 2013)
The paper explores the relationship between accounting information and stock returns of the companies listed on the Athens Stock Exchange (ASE) in the period 1998–2008. Publicly available financial data on the companies included in the ASE during 1998–2008 have been collected and processed. The data sample consists of 245 companies and varies from 2,166 to 1,441 firm-year observations. The research methodology has been based on the extension of the model introduced by Kothari and Sloan (1992) and investigates whether the level of earnings divided by price at the beginning of the stock return period is associated with returns in the context of ‘prices lead earnings’ using annual and quarterly data. Cross-sectional regression analysis points to a significant relationship between earnings and returns on measurement windows of one year and longer. Similar results have been found in the case of a cumulative model where earnings are aggregated up to four years; however, relationship in the short measurement window up to three quarters has resulted in low earnings response coefficients.